Towards an Engaged Pedagogy: Bell Hooks Manifesto and the Teaching and Learning of Mathematics (Global Journal of Human-Social Science, 2013)
The debate over what content and methods should compose the mathematics education of children has been an omnipresent contested discourse in the mathematics education terrain In today s schooling regimes the push for accountability and the movement towards a culturally-coded standards based curriculum seem to cripple every earnest attempt at rejuvenation and redemption of democratic access to educational opportunities and resources for learners The abysmal inequalities we witness in schools and societies worldwide have been complicit in creating a rather apocalyptic vision of the future of education as a practice of engagement and empowerment With a longstanding history that imbibed racial demarcation and reductionist positioning the quest for liberation through transformative education endeavors appears as if a figment of pure imagination In the face of intensified challenges that transcend national geographic boundaries we seek refuge and inspiration by revisiting the works of crucial thinkers such as bell hooks who reminds us of the ultimate goal of education viz praxis of humanization and liberation